Table of Contents (Law, State and Telecommunications Review, 2023)
We are delighted to include articles on Kazakhstan's electronic money trends and the need legal reforms for its proper functioning and circulation; the evolution of regulatory debates on internet interoperability and network access through case studies from the United States and Europe; the right to be forgotten in digital law, with a focus on European Union Court of Justice and European Court of Human Rights decisions; the legal solutions for defining robots in civil relations and establishing effective regulations for robotics usage in Ukraine; the use of artificial intelligence in the Ukrainian Judicial System; the legal aspects of digital face identification technology in criminal proceeding in Ukraine, China's artificial intelligence-driven social credit system's impact on international human rights, particularly concerning privacy issue; the role of electronic money in modernizing Kazakhstan's monetary system; the development of a cyber-crime protection system in Indonesia, including cyber insurance regulations; the impact of digital transition and its intensification during crises like the COVID-19 Pandemic and the Ukraine War on the tourism industry in the European Union; the prevention of cyber sabotage in Ukraine and the control of its damages; and the standardization of cybersecurity threat terminology on a global scale.